ARTIFICIAL INTELLIGENCE IN SPORTS SCIENCE - A BIBLIOMETRIC ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Artificial intelligence start role the sports industry. This study focusto conduct the bibliometric analysis in sports science area. To achieve the purpure data were collected from the Web of Science data base. By using the Mesh term found 74740 articles found in the artificial intelligence. Based on the inclusion and exclusion criteria 23 articles finalized for analysis in the area of sports science. By using RStudio bibloshiny analysis we found very few studies were found in the areas of Artificial intelligence in sports science. It is recommended to more research need to conduct in future for improving sports performance with the help of artificial intelligence